Measuring Unilateral Effects under Data Scarcity: A Merger Case in South Africa - (:unkn) unknown (My University, 2020)
In this paper, we use a differentiated-products setup to assess the impact on competition of a merger between Greif and Rheem South Africa. Both parties are active in the industrial packaging products sector. The parties’ activities overlap, among others, in the production of large steel drums. Our analysis suggests that there is a low degree of substitutability between large steel drums and other products in the market. For this reason, we focus our competitive assessment on the unilateral effects of large steel drums. We rely on a limited amount of relatively high-level data to arrive to robust conclusions on the unilateral effects that the merger would induce. We study these unilateral effects using two empirical tools, the upward pricing pressure (UPP) and the gross upward pricing pressure index (GUPPI). These two measures are complementary in assessing the competitive harm that the merger could induce. UPP nets out the incentive to raise prices due to lower competition with the incentive to reduce prices due to lower marginal costs. GUPPI focuses on the incentive to raise prices post-merger and is linked to the market definition that competition authorities use when defining the relevant market. To our knowledge, this paper provides the first application in the African continent of such empirical analysis. We calculate these two measures following the conclusion of the Tribunal. We conclude that both UPP and GUPPI consistently signal that the merger would create strong incentives to raise prices.
Keywords: African Research